LEGALITY ISSUANCE OF FAMILY CARD IN SIRI MARRIAGE - Cholidatul Rizky Amalia; Anggia Vionita Rachman; Nabilla Yahya; Nadya Nur Ivany (STIH Putri Maharaja, 2022)
The issuance of Family Cards for unregistered marriages submitted by the Director General of Population and Civil Registry of the Ministry of Home Affairs has caused a polemic in Indonesian positive law, because the statement is not in accordance with the regulations of Law Number 1 of 1974. In this regulation it has been stated that marriages are considered valid by The State if it is carried out in accordance with religion and registered with an authorized official, for this reason, unregistered marriage is not recognized by the State because its implementation is not in accordance with existing provisions. The Director General of Population and Civil Registry of the Ministry of Home Affairs provides the possibility for those who have unregistered marriages to get a Family Card. This study uses a normative juridical research method based on the laws and regulations in Indonesia, as well as legal concepts. The results of this study regarding the validity of the issuance of Family Cards for unregistered marriages, it can be concluded that the perpetrators of unregistered marriages have violated the recording. Thus, the marriage is not completedonlywith the marriage contract, but must also be recorded. And the legal consequences of the issuance of family cards in unregistered marriages will only support the decisions of individuals who will carry out unregistered marriages.